New ankylosaur (Thyreophora, ornithischia) remains from the Upper Cretaceous of Patagonia - Murray, Alejandro; Riguetti, Facundo Javier; Rozadilla, Sebastian (Journal of South American Earth Sciences)
Fossil evidences of the presence of ankylosaurian dinosaurs in Gondwana are scarce but consistent, being found in Antarctica, Oceania and South America. In spite that there are no nominated species in South America, the ankylosaur fossil record has increased in the last years. Indeterminate nodosaurid specimens, some isolated osteoderms and many trackways are known from the Upper Cretaceous of South America. The aim of the present contribution is to report new ankylosaurian remains from the Allen Formation (Campanian-Maastrichtian) at the Salitral Moreno locality, Northern Patagonia, Argentina. These osteoderms are small and conical, and includes thoracic, sacral and caudal scutes. The thoracic and sacral pieces are similar to those belonging to nodosaurids. The caudal osteoderm is a new element for the record of South American ankylosaurs. It resembles the caudal plates of Kunbarrasaurus and some ankylosaurids. The scutes show a mixture of characters so it is not possible to assign these pieces to a nodosaurid-like or ankylosaurid ankylosaur. These elements are consistent with the previously known ankylosaur fossil record of the Upper Cretaceous of Argentina, being a new sample of the diversity of the latest Cretaceous from South America. Fil: Murray, Alejandro. Fundación de Historia Natural Félix de Azara; Argentina Fil: Riguetti, Facundo Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fundación de Historia Natural Félix de Azara; Argentina Fil: Rozadilla, Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina